The healthy weight research network: a research agenda to promote healthy weight among youth with autism spectrum disorder and other developmental disabilities. Issue 1 (24th February 2016) - Curtin, C.; Must, A.; Phillips, S.; Bandini, L.
Summary: The Healthy Weight Research Network (HWRN) for children with autism and developmental disabilities is an interdisciplinary network with national representation. This paper discusses the modified Delphi procedure that was used to develop the HWRN's research agenda to address the problem of obesity in children with autism and developmental disabilities. The five research areas identified for priority included: (i) family practices around food/mealtimes; (ii) physical activity and sedentary behaviours in relation to weight; (iii) relationship between food patterns, behaviour and weight gain; (iv) programme‐adaption and delivery; and (v) influence of school and community‐based organizations on food intake and physical activity. The goals and agenda of the HWRN hold promise for making progress toward the prevention and successful treatment of obesity in this population.